The rise of registry-based research: a bibliometric analysis. (8th October 2021) - Romanini, Emilio; Schettini, Irene; Torre, Marina; Venosa, Michele; Tarantino, Alessio; Calvisi, Vittorio; Zanoli, Gustavo
Abstract : Background and purpose — The main purpose of arthroplasty registries is to collect information on patients, techniques, and devices to monitor and improve the outcome of the specific procedure. This study analyses the role played by registries in the orthopedic research community and describes publication trends, characteristics, and patterns of this field of research. Patients and methods — A descriptive-bibliometric review was conducted. Scopus was the database used for the research. All articles published from 1991 to December 2020 containing keywords related to registries and arthroplasty were considered. In particular, the following dimensions were analyzed in detail: (i) papers/year; (ii) journals; (iii) countries; (iv) research growth rate; (v) collaboration among countries. VOSviewer software was used to perform the bibliometric analysis. Finally, the 50 most cited papers of the last 10 years were briefly analyzed. Results — 3, 933 articles were identified. There has been growing interest in the topic since 2010. Acta Orthopaedica ranked first for the number of articles published. The country with the largest number of articles citing registries was the United States, followed by the United Kingdom and Sweden. The relative number of articles per 100, 000 inhabitants is 0.60 for Europe and 0.38 for the United States. The literature in this research area has an average yearly growth rate of 28%. Interpretation — The publication rate in the field of arthroplasty registries is constantly growing with a noteworthy impact in the evolution of this research and clinical area. The growth rate is significantly higher than that of arthroplasty literature (28% vs. 10%) and the collaboration among countries is strong and increasing with time.